Relationship between spirituality and social media addiction among adults - Demiroğlu, Birsen; Taş, Besra; Taş, Besra (Bülent DİLMAÇ, 2021)
In recent years, with the rapidly developing and changing technology, it is seen that many users of all ages have entered into new searches and spent a long time of their lives in social media areas, and these applications have a great impact on people. Based on this idea, no study on adult spirituality and social media addiction was found in the literature review, and it was studied with the thought that this study would be beneficial in the literature. In this study, it was aimed to examine the relationship between adults' spirituality and social media addiction levels. Correlation method, one of the Quantitative Research models, was used in the study. The study group of the research consists of 724 adult individuals living in the metropolis located in the west of Turkey.. "Spirituality Scale", "Social Media Addiction Scale - Adult Form" and "Personal Information Form" were used to collect data. As a result of the research, a statistically significant relationship was found between the scores of the spirituality scale and the scores of the social media addiction scale. It was observed that as the spirituality scale score increased, the social media addiction scale score decreased.
Keywords: Spirituality; Social media; Addiction; Social media addiction